The Development And The Effectiveness Of Trauma Focused Schema Therapy (Tf-St) On Malaysian Female Young Adults With Symptoms Of Post-Traumatic Stress Disorder (Ptsd) - Lian, Amos En Zhe (2023)
In phase one of the study, these limitations were addressed through assimilative integrating trauma psychoeducation, psychodynamic techniques, and art therapy. This newly integrated schema therapy is named ‘trauma-focused schema therapy’ (Tf-ST). In phase two, the present study conducted an interventional randomised controlled trial (RCT) to investigate the effectiveness of the Tf-ST developed in phase one, with female young adults in Malaysia who experienced repeated and continuous trauma. The results support that the newly developed Tf-ST is a viable option for repeated and continuous trauma intervention in Malaysia. Thus, the present study encourages the clinical and research field to keep improving and developing alternative or more advanced psychotherapy, rather than fixating on previously established trauma interventions such as Tf-CBT.